Optimalisasi Kebutuhan Tenaga Kerja Produksi dengan Metode Stopwatch Time Study - Syafaat Auladi; Putri Azzahra; Tuwandi Juniarto (Jurnal Teknik Ibnusina, 2026)
CV Panca Konveksi faces excessive workload due to limited workforce, which results in production delays and financial losses. This study aims to determine the optimal number of workers using the Stopwatch Time Study method. Data were obtained through direct observation of three work elements in the sewing process, namely body sewing, sleeve sewing, and neck sewing, which were analyzed using uniformity tests, data sufficiency tests, performance ratings, and allowances. The results showed that two existing workers bear a workload of more than 150%. Calculations based on standard time indicate that the optimal workforce requirement is three people so that the workload is at the ideal level of 100%. This study concludes that standard time-based work measurement can be an objective basis for workforce planning to increase efficiency and reduce dependence on external production.